Pengaruh Kompetensi Dosen, Self Efficacy, Locus Of Control, dan Fasilitas Pembelajaran terhadap Tingkat Pemahaman Mahasiswa Akuntansi di Universitas Katolik Widya Mandala Madiun - Rubiantoro, Surya Agung; Rustyaningsih, Sri; Mujilan, Mujilan (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2019)
This study aims to demonstrate empirically the effects of lecture’s competency, self-efficacy, locus of control, and learning facilities of the level of accounting student understanding. Data was collected by spreading the questionnaire. The samples used were 111 accounting students of Faculty of Economics and business of Catholic University of Widya Mandala Madiun. The sampling method used were purposive sampling. Data analysis method used were multiple linear regression analysis test with SPSS version 17. The results of this research show that lecture’s competency, self-efficacy, locus of control, and learning facilities has now effects to the level of accounting student understanding